2014
DOI: 10.1016/j.jval.2014.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Patient Preferences for Treatment of Low Back Pain—A Discrete Choice Experiment

Abstract: The majority of the respondents prefer nonsurgical interventions, but patients are willing to wait for more ideal outcomes and preferred interventions. The results show that health care professionals have a very important task in communicating clearly about the expected results of treatment and the basis of their treatment decisions, as patients' preferences are highly individual.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 53 publications
(55 reference statements)
1
60
0
Order By: Relevance
“…Unsurprisingly, majority of the respondents prefer nonsurgical interventions, but patients are willing to wait for more ideal outcomes and preferred interventions. The attributes for eliciting patients’ preference between invasive surgery and conservative non-surgical treatments, including risk of relapse, reduction in pain, and expected increase in the ability to perform activities of daily living, are different from our study that explored choices between non-surgical treatments, and hence the results are not comparable [ 52 ].…”
Section: Discussionmentioning
confidence: 90%
“…Unsurprisingly, majority of the respondents prefer nonsurgical interventions, but patients are willing to wait for more ideal outcomes and preferred interventions. The attributes for eliciting patients’ preference between invasive surgery and conservative non-surgical treatments, including risk of relapse, reduction in pain, and expected increase in the ability to perform activities of daily living, are different from our study that explored choices between non-surgical treatments, and hence the results are not comparable [ 52 ].…”
Section: Discussionmentioning
confidence: 90%
“…The duration of back pain was either undefined or mixed in 39 (78%) studies[ 24 , 25 , 37 43 , 45 47 , 50 , 51 , 55 65 , 67 69 , 72 77 , 79 81 , 83 , 84 ] . While 11 (22%) studies reported on chronic back pain (>12 weeks duration)[ 44 , 48 , 49 , 52 54 , 66 , 70 , 71 , 78 , 82 ].there were no studies on acute back pain alone (<6 weeks duration).…”
Section: Resultsmentioning
confidence: 99%
“…There were 35 qualitative studies[ 25 , 37 , 38 , 40 46 , 48 54 , 59 61 , 65 69 , 71 , 74 , 75 , 77 79 , 81 84 ] with participant numbers ranging from 7 to 110, with a median of 23. There were 14 quantitative studies[ 24 , 39 , 47 , 55 58 , 62 64 , 70 , 72 , 73 , 76 , 80 ], with a median participant number of 628 (range 124–1555). Mixed methods were utilised in 1 study[ 70 ], which had 348 participants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also a reasonable assumption that patient expectations and preference for a specific treatment are closely related, however involve complex interactions that require further investigation through adequately powered studies 16,17. These findings also reinforce the important role health care providers have when communicating clinical decision-making processes with patients in regard to expected outcomes and personal preferences as conflicts have potential to influence outcomes 14,15,18…”
Section: Treatment Preference and Experienced Pain Reliefmentioning
confidence: 74%